1993
DOI: 10.1246/cl.1993.1141
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Isomerization of n-Butane Catalyzed by an Acidic Cesium Salt of 12-Tungstophosphoric Acid

Abstract: A salt of H3PW12O40, Cs2.5H0.5PW12O40, catalyzed efficiently the skeletal isomerization of n-butane to isobutane at 300 °C. The activity and selectivity were much higher than those of SO22−/ZrO2. H-ZSM-5 was more active than Cs2.5H0.5PW12O40, but the selectivity was very low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 9 publications
1
17
0
Order By: Relevance
“…The surface acidities of Cs 2.5 H 0.5 W and H 3 W were 43 and 17 µmol g −1 , respectively. Koyano et al (13) and Na et al (14) reported that the surface acidity of Cs x H 3-x W initially decreased from x = 0 to 2, where at x = 0 and x = 2, the surface acidity was 14 and 0.4 µmol g −1 , respectively. When H + was substituted by Cs + , at x = 2.5, the surface acidity was 60 µmol g −1 before dropping to zero at x = 3 (13).…”
Section: Resultsmentioning
confidence: 99%
“…The surface acidities of Cs 2.5 H 0.5 W and H 3 W were 43 and 17 µmol g −1 , respectively. Koyano et al (13) and Na et al (14) reported that the surface acidity of Cs x H 3-x W initially decreased from x = 0 to 2, where at x = 0 and x = 2, the surface acidity was 14 and 0.4 µmol g −1 , respectively. When H + was substituted by Cs + , at x = 2.5, the surface acidity was 60 µmol g −1 before dropping to zero at x = 3 (13).…”
Section: Resultsmentioning
confidence: 99%
“…[29][30][31] From the synthetic point of view, the typical procedure for preparation of cesium salts of HPAs are generally proceeded through a solution method by titrating the controlled amount of an aqueous solution of Cs 2 CO 3 into the aqueous solution of HPA. [32,33] In the previous report we found that the solid synthesis method by ball milling of HPA with CsNO 3 at room temperature is much simpler than the solution method, which is convenient to control the cesium content and has great potential in large scale preparation. [34] In the present work, cesium salts of vanadium-substituted molybdophosphoric acid, Cs x H 3 + n -x PMo 12 -n V n O 40 (n=0, 1, 2, x=0.5-3.0), have been prepared by the solid synthesis method.…”
Section: Introductionmentioning
confidence: 99%
“…Suzuki et al [13] observed that Pd x H 3-2x PW 12 O 40 /SiO 2 catalyzed n-hexane isomerization in the presence of hydrogen. Na et al [14,15] found that an acidic Cs salt of H 3 PW 12 O 40 , namely Cs 2.5 H 0.5 PW 12 O 40 , was very active and selective for the n-butane skeletal isomerization. Besides the application of heteropoly acid salts, heteropoly acids (HPAs), in particular those with Keggin structure H 8-x [X x+ M 12 O 40 ] (X = P 5+ or Si 4+ , M = W 6+ or Mo 6+ ), which are strong brønsted acids were also extensively used as acid catalysts [16].…”
Section: Introductionmentioning
confidence: 99%